2013
DOI: 10.1007/s00414-013-0916-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an individual's age on the amount and interpretability of DNA left on touched items

Abstract: In crime scene investigations, DNA left by touch on an object can be found frequently and the significant improvements in short tandem repeat (STR) amplification in recent years built up a high expectation to identify the individual(s) who touched the object by their DNA profile. Nevertheless, the percentage of reliably analysable samples varies considerably between different crime scenes even if the nature of the stains appears to be very similar. Here, it has been proposed that the amount and quality of DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 19 publications
4
25
1
3
Order By: Relevance
“…No variables other than gender could be clearly identified by the LCA as being associated with individuals who had a stronger probability to carry high amounts of DNA on their hands, with the partial exception of the absence of a tendency to touch or to play with hair. In particular, no clear subdivision was found in relation to age, which has recently been described as a factor that may possibly influence the extent of DNA transfer [40].…”
Section: Discussionmentioning
confidence: 73%
“…No variables other than gender could be clearly identified by the LCA as being associated with individuals who had a stronger probability to carry high amounts of DNA on their hands, with the partial exception of the absence of a tendency to touch or to play with hair. In particular, no clear subdivision was found in relation to age, which has recently been described as a factor that may possibly influence the extent of DNA transfer [40].…”
Section: Discussionmentioning
confidence: 73%
“…Some authors have reported increased DNA "shedding" or "sloughing" in men versus women [44], and in young males compared to older ones (the same trend was not observed in females), but significantly, over ¾ of subjects changed status (good/ intermediate/ poor) between trials three days apart [45]. Others concluded that while children are typically "better" shedders and the elderly somewhat "worse," adults in the categories in between are significantly less predictable [46]. Although high intra-and inter-individual variation is consistently reported [47,48], many authors report that those subjects whose handled items yield either more or better quality DNA are a quantifiable group [44,47,49,50].…”
Section: Amounts Of Trace Dnamentioning
confidence: 97%
“…Skin conditions that increase the proliferation rate of the skin cells, such as dermatitis and psoriasis, may also result in the deposition of higher quantities of DNA through touch [116]. Further, studies have shown that younger individuals tend to deposit greater quantities of DNA compared to those that are older [117,118], while males may be more likely to be classified as heavy shedders compared to females [105,117,119]. Determining the extent to which genetic factors and various non-genetic factors (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%